Graphene Oxide "Surfactant"‐Directed Tunable Concentration of Graphene Dispersion. Issue 45 (20th October 2020) - Luo, Jiajun; Yang, Liangwei; Sun, Danping; Gao, Zhenfei; Jiao, Kun; Zhang, Jin
Abstract: Homogeneous graphene dispersions with tunable concentrations are fundamental prerequisites for the preparation of graphene‐based materials. Here, a strategy for effectively dispersing graphene using graphene oxide (GO) to produce homogeneous, tunable, and ultrahigh concentration graphene dispersions (> 150 mg mL −1 ) is proposed. The structure of GO with abundant edge‐bound hydrophilic carboxyl groups and in‐plane hydrophobic π‐conjugated domains allows it to function as a special "surfactant" that enables graphene dispersion. In acidic solutions, GO sheets tend to form edge‐to‐edge hydrogen bonds and expose the π‐conjugated regions which interact with graphene, thereby promoting graphene dispersion. While in alkaline solutions, GO sheets tend to stack in a surface‐to‐surface manner, thereby blocking the π‐conjugated regions and impeding graphene dispersion. As the concentration of GO‐dispersed graphene dispersion (GO/G) increases, a continuous transition between four states is obtained, including a dilute dispersion, a thick paste, a free‐standing gel, and a kneadable, playdough‐like material. Furthermore, GO/G can be applied to create desirable structures including highly conductive graphene films with excellent flexibility, thereby demonstrating an immense potential in flexible composite materials. Abstract : Graphene dispersions with homogeneous, stable, and ultrahigh concentration are prepared by using graphene oxide (GO) as a special "surfactant" in aqueous solution. GO interacts with graphene through π–π interactions and is sensitive to the solution pH values. The graphene dispersion can be used to form 1D graphene fibers, 2D graphene films, and 3D graphene doughs through material‐processing techniques.